Skandinavisk kobber Lokale forhold og globale sammenhenger i det lange 1700-tallet - Ranestad, Kristin; Bruland, Kristine (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
Copper is an ancient product that has persisted into the advanced industrial age. Its production methods and uses have been radically transformed several times, and it has played a central role in the building of the modern world economy. Despite this, it has been neglected by historians. For many years in early modern Europe Scandinavia was the biggest producer of copper, particularly through the large copper plants at Røros in Norway and in Falun in Sweden. This book tells the story. The amount of copper produced and traded is investigated, working conditions are discussed, the organisation of the companies is clarified, the active role of the state is emphasised, and the influence of the copper industry on local conditions is explored. The book gives copper an important place in European industrialisation more generally and shows that the Scandinavian copper industry was part of an extensive European copper network, which in turn was part of a global manufacturing and trading system. Through such connections, the Scandinavian copper industry was linked closely to the international and global history of copper, and therefore to colonialism, industrialisation, slavery and violence.